When water is thicker than blood: recognising a systemic cause of haemoptysis. Issue 4 (25th October 2016) - Wedge, Eileen; Abrahamson, Ed; Tudor-Williams, Gareth; Nadel, Simon; Deal, Jane
Abstract : The case of an 11-year-old child presenting with acute haemoptysis and breathlessness is described. The girl was Malaysian and had recently arrived in the UK. She subsequently deteriorated, developing respiratory failure. The course of the illness is described, with reference to the diagnostic process at each stage. The case demonstrates the importance of having a broad investigatory approach in acute haemoptysis.